Activated Amorphous Carbon With High-Porosity Derived From Camellia Pollen Grains as Anode Materials for Lithium/Sodium Ion Batteries - Xu, Kaiqi; Li, Yunsha; Xiong, Jiawen; Ou, Xing; Su, Wei; Zhong, Guobin; Yang, Chenghao (Frontiers in Chemistry, 2018)
Carbonaceous anode materials are commonly utilized in the energy storage systems, while their unsatisfied electrochemical performances hardly meet the increasing requirements for advanced anode materials. Here, activated amorphous carbon (AAC) is synthesized by carbonizing renewable camellia pollen grains with naturally hierarchical structure, which not only maintains abundant micro- and mesopores with surprising specific surface area (660 m2 g−1), but also enlarges the interlayer spacing from 0.352 to 0.4 nm, effectively facilitating ions transport, intercalation, and adsorption. Benefiting from such unique characteristic, AAC exhibits 691.7 mAh g−1 after 1200 cycles at 2 A g−1, and achieves 459.7, 335.4, 288.7, 251.7, and 213.5 mAh g−1 at 0.1, 0.5, 1, 2, 5 A g−1 in rate response for lithium-ion batteries (LIBs). Additionally, reversible capacities of 324.8, 321.6, 312.1, 298.9, 282.3, 272.4 mAh g−1 at various rates of 0.1, 0.2, 0.5, 1, 2, 5 A g−1 are preserved for sodium-ion batteries (SIBs). The results reveal that the AAC anode derived from camellia pollen grains can display excellent cyclic life and superior rate performances, endowing the infinite potential to extend its applications in LIBs and SIBs.